2016
DOI: 10.1016/j.neuroscience.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Short-term environmental enrichment enhances synaptic plasticity in hippocampal slices from aged rats

Abstract: Age-associated changes in cognition are mirrored by impairments in cellular models of memory and learning, such as long-term potentiation (LTP) and long-term depression (LTD). In young rodents, environmental enrichment (EE) can enhance memory, alter LTP and LTD, as well as reverse cognitive deficits induced by aging. Whether short-term EE can benefit cognition and synaptic plasticity in aged rodents is unclear. Here, we tested if short-term EE could overcome age-associated impairments in induction of LTP and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 94 publications
3
35
2
Order By: Relevance
“…VEGF encourages hippocampus-dependent memory independently of its effects on neurogenesis and angiogenesis, by increasing the synaptic strength [68,69]. Recent studies have been reported that short-term exposure to EE is also enough to alter synaptic plasticity and molecular markers related to the cognitive function [4]. EE-facilitated LTP was dependent upon NMDA receptors.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
See 3 more Smart Citations
“…VEGF encourages hippocampus-dependent memory independently of its effects on neurogenesis and angiogenesis, by increasing the synaptic strength [68,69]. Recent studies have been reported that short-term exposure to EE is also enough to alter synaptic plasticity and molecular markers related to the cognitive function [4]. EE-facilitated LTP was dependent upon NMDA receptors.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…Physical exercise exposure has been shown to increase object recognition memory and to encourage BDNF expression in rats [30,34], and the relations of EE and exercise on sensory gating and spatial memory has been formerly reported in rodents [30,35]. In rodents, EE can improve memory and long-term potentiation (LTP) [4]. Another study described that BDNF is increased following EE, and this EE-induced BDNF goes with the enhancement of the object recognition memory and the improvement of LTP [5].…”
Section: Brain-derived Neurotrophic Factor (Bdnf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the simplicity of this manipulation, environmental enrichment has been repeatedly shown to provide numerous structural and functional benefits to the hippocampus (Clemenson, Gage, & Stark, 2018). Importantly, environmental enrichment has been shown to improve both structural and cognitive deficits associated with aging, such as increased neurogenesis (Kempermann, Gast, & Gage, 2002;Leal-Galicia, Castañeda-Bueno, Quiroz-Baez, & Arias, 2008;Segovia, Yagüe, García-Verdugo, & Mora, 2006;Speisman et al, 2013), dendritic branching and spine density (Darmopil, Petanjek, Mohammed, & Bogdanović, 2009), expression of presynaptic proteins (Frick & Fernandez, 2003;Leal-Galicia et al, 2008;Saito et al, 1994), neurotransmitter release (Segovia et al, 2006), enhanced long-term potentiation and depression (Kumar, Rani, Tchigranova, Lee, & Foster, 2012;Stein, O'Dell, Funatsu, Zorumski, & Izumi, 2016), and related hippocampus-dependent behaviors (Kempermann et al, 2002;Segovia et al, 2006;Speisman et al, 2013). Whether the benefits of environmental enrichment are due to physical activity (Kobilo et al, 2011;Mustroph et al, 2012;van Praag, Kempermann, & Gage, 1999), spatial exploration (Freund et al, 2013), learning (Gould, Beylin, Tanapat, Reeves, & Shors, 1999;Leuner et al, 2004), or other aspects of the environment (Birch, McGarry, & Kelly, 2013;Steiner, Zurborg, Hörster, Fabel, & Kempermann, 2008), the surrounding environment can have a significant impact on the aging hippocampus of animals.…”
Section: Introductionmentioning
confidence: 99%